Biomechanical Characteristics of Long Stair Climbing in Healthy Young Individuals in a Real-World Study Using a Wearable Motion Analysis System - Yaguchi, Haruki; Sekiguchi, Yusuke; Honda, Keita; Fukushi, Kenichiro; Huang, Chenhui; Nakahara, Kentaro; Zhenzhao, Cheng; Izumi, Shin-Ichi (Biomechanics (Basel, Switzerland), 2022)
Background: Stair climbing is a part of the basic activities of daily living. Previous biomechanical analyses of stairs have been conducted in the laboratory, resulting in only a few steps. Therefore, the biomechanical characteristics of long stair climbing in the real world remain unclear. The purpose of this study was to identify differences in kinematic and kinetic in the lower limb between the beginning and end phases of long stair climbing in an outdoor environment using a wearable motion analysis system. Eight subjects (four males and four females) were included in the data analysis (age: 23.6 ± 0.5 years). The long stair was 66 consecutive steps out of 202 stone steps. A wearable motion analysis system comprised six inertial measurement units and foot pressure sensors. The maximum ankle joint flexion angle in the end phase was significantly increased more than in the beginning phase (p < 0.001). On the other hand, the other kinematic, kinetic, and stair climbing speeds showed no significant difference between the phases. The findings indicated that fatigue during long stair climbing might increase ankle dorsiflexion to compensate for forwarding propulsion.